Facile synthesis of PdSn alloy octopods through the Stranski–Krastanov growth mechanism as electrocatalysts towards the ethanol oxidation reaction. Issue 17 (6th April 2022) - Huang, Jingbo; Ji, Liang; Li, Xiao; Wu, Xingqiao; Qian, Ningkang; Li, Junjie; Yan, Yucong; Yang, Deren; Zhang, Hui
Abstract : Pd72 Sn28 octopods synthesized through the Stranski–Krastanov growth mode exhibited remarkably enhanced catalytic performance for the EOR relative to commercial Pd/C. Abstract : Pd-based nanocatalysts are critical to the commercialization of direct ethanol fuel cells (DEFCs); however, the synthesis of Pd-based binary alloy nanocrystals with well-defined branches is still a great challenge. Here we report a facile seed-mediated approach for the synthesis of PdSn alloy octopods with precisely controlled branches and tunable compositions through the Stranski–Krastanov growth mode. The PdSn octopod-like catalysts exhibited prominently enhanced catalytic activity and stability towards the ethanol oxidation reaction (EOR) with respect to commercial Pd/C in alkaline solution. Specifically, Pd72 Sn28 octopods exhibited the highest mass and specific activities (2701 mA mg −1 and 11.27 mA cm −2 ), which were 2.1 and 6.7 times higher than those of commercial Pd/C, respectively. Density functional theory (DFT) calculations reveal that the lowest d-band center of the (100) surface of Pd72 Sn28 weakens the adsorption of the acetate-evolution key intermediate *CH3 CO, leading to the best catalytic activity towards the EOR.